WHEN NO SCHOOL IS OPEN FOR LEARNING: DOES VIRTUAL TEACHING PRACTICE MEET EFL PRE-SERVICE TEACHERS’ NEED? - Fika Megawati; Nur Mukminatien; Niamika El Khoiri (Universitas Muhammadiyah Semarang, 2021)
Covid-19 pandemic has transformed teacher education programs to shift their academic activities for pre-service teachers. Accordingly, teaching practice are mostly carried out virtually in order to get access to the school learning. This study aims at exploring pre-service teachers’ experiences in fulfilling their needs in online classroom instruction during Covid-19 emergency remote teaching (ERT). Five pre-service teachers were involved in this study. To collect the data, interview transcripts and teaching artefacts were analyzed qualitatively. The result of this study show three important points. First, to find out raw model, students’ response, school environment and culture, and teaching performance, they were not completely obtained in virtual class. Second, learning process can be carried out effectively if the pre-service teachers and students were supported by sufficient stuffs for doing online. In relation to the platform, there is no single best technology was implemented. Third, pre-service teachers’ digital literacy were important to adapt the school policy and to accommodate the learners’ situation. In a nutshell, this study implies that the attention in assisting pre-service teachers to face emergency remote situation in their field experience is important to be evaluated.